Verapamil chronicles: advances from cardiovascular to pancreatic β-cell protection - Arefanian, Hossein; Koti, Lubaina; Sindhu, Sardar; Ahmad, Rasheed; Al Madhoun, Ashraf; Al-Mulla, Fahd (Frontiers in Pharmacology, 2023)
Verapamil is a well-known drug used for treating angina and hypertension. Emerging data from current clinical trials suggest that this calcium channel blocker has a potential benefit for pancreatic β-cells through the elevation and sustenance of C-peptide levels in patients with diabetes mellitus (DM). This is intriguing, given the fact that the current therapeutic options for DM are still limited to using insulin and incretins which, in fact, fail to address the underlying pathology of β-cell destruction and loss. Moreover, verapamil is widely available as an FDA-approved, cost-effective drug, supported also by its substantial efficacy and safety. However, the molecular mechanisms underlying the β-cell protective potentials of verapamil are yet to be fully elucidated. Although, verapamil reduces the expression of thioredoxin-interacting protein (TXNIP), a molecule which is involved in β-cell apoptosis and glucotoxicity-induced β-cell death, other signaling pathways are also modulated by verapamil. In this review, we revisit the historical avenues that lead to verapamil as a potential therapeutic agent for DM. Importantly, this review provides an update on the current known mechanisms of action of verapamil and also allude to the plausible mechanisms that could be implicated in its β-cell protective effects, based on our own research findings.